Relationship of Torch Profile in First Trimester Spontaneous Miscarriage - Lamichhane, Sabina; Subedi, Shanti; Pokharel Ghimire, Sita; Chetri, Manisha; Banerjee, Basudev (Journal of Nobel Medical College, 2016)
Background TORCH is a group of organisms like Toxoplasma, Rubella, Cytomegalo virus and Herpes simplex virus. These groups of organisms causing infections in pregnant lady leads to various degree of adverse pregnancy outcomes in the form of spontaneous abortion, preterm delivery, intrauterine growth restriction, severe congenital defect with syndromic babies. So, to observe the relationship of TORCH infection in first trimester spontaneous miscarriage in our population and to treat them, this study was performed. Materials and Methods A total of 103 patients with spontaneous abortion meeting inclusion criteria were taken in the study. TORCH profile was sent for those patients and observed the sero-prevalance for IgM and IgG. Thereafter organism was identified and the results were interpreted. Results Out of total 103 patients enrolled 58.25 % of patients were sero-positive for TORCH complex. IgM or IgG Sero-positive for Toxoplasma, Rubella, Cytomegalo virus and Herpes Simplex virus were 11.65% /17.47% ;7.76% / 43.68%; 19.41% / 41.74% and 31.06% / 54.36% respectively. Conclusion In the present study on analyzing the association of TORCH antibodies in women with spontaneous abortion, infection with Herpes simplex virus was most commonly associated. Journal of Nobel Medical College Vol.5(2) 2016; 17-21